Effects of Climate Change Adaptation Strategies on Food Crop Production in North East Nigeria - Tammi, Hajjatu; Headboy, Philemon; Wazakari , Rogers Roland (Kashere Journal of Politics and International Relations, 2025)
The study examines the impact of climate change adaptation strategies on the efficiency of food crop production in northeastern Nigeria. Adaptation strategies, including changes in agricultural practices and systems, are acknowledged as crucial for farmers to cope with climate variability. These strategies aim to boost productivity, efficiency, and economic returns from farming. The research utilized a multi-stage sampling method to select 120 respondents, with data gathered via a structured questionnaire and analysed through both descriptive and inferential statistics. The sampling techniques included purposive sampling across the six states of Northeast Nigeria Adamawa, Borno, Yobe, Taraba, Bauchi, and Gombe. Descriptive statistics, such as percentages and frequencies, were employed, and a Multinomial Logit model was used to estimate the likelihood of achieving the study's objectives. Regression analysis indicated that factors such as marital status, age, education level, farming experience, farm size, access to extension services, and extension visits had positive and statistically significant effects (P<0.01) on adaptation. Major barriers to adopting climate change adaptation strategies among food crop farmers included high input costs, insufficient financial resources, labour costs, and inadequate climate information. The study concludes that farmers' socio-economic characteristics significantly influence their perceptions and adaptation to climate change. The study recommends the government and policymakers should broaden service coverage and improve service quality to address climate change-related risks, with special attention to disadvantaged groups such as poor farmers in remote areas, and extension agents should intensify efforts to raise awareness and educate farmers about climate change.